Peran Kepuasan dalam Menguji Word-of-Mouth pada Pelanggan Market Place - Septiamah, Sindyh; Setyowati, Indah Amelia Putri; Astuti, Widia Puji; Halimah, Winda; Suhud, Usep (Jurnal Bisnis, Manajemen, dan Keuangan, 2020)
This study aims to examine the factors that influence word-of-mouth in the consumer market place. In this case, there are five variables used to measure, namely word-of-mouth, trust, satisfaction, purchase intention, and loyalty. Data collection was carried out in Jakarta during the PSBB (Large-Scale Social Limitation) period in April - May 2020. Data was collected using an online questionnaire and respondents were selected using a purposive sampling technique. The total respondents in this study were 250 consisting of 91 men and 159 women. Data were processed using exploratory factor analysis and structural equation models. The result, trust has a positive and significant effect on satisfaction, trust has a positive and significant effect on word-of-mouth, purchase intention has a positive and significant effect on loyalty, word of mouth has a positive and significant effect on purchase intention. While satisfaction variable does not have a significant effect on purchase intention, satisfaction does not have a significant effect on word of mouth, and loyalty does not have a significant effect on word-of-mouth.